Absence of the adaptor protein Shb potentiates the T helper type 2 response in a mouse model of atopic dermatitis. Issue 1 (September 2014) - Gustafsson, Karin; Willebrand, Elsa; Welsh, Michael
Summary Aberrant regulation of T helper (Th) cell maturation is associated with a number of autoimmune conditions, including allergic disorders and rheumatoid arthritis. The Src homology domain protein B (Shb) adaptor protein was recently implicated as a regulator of Th cell differentiation. Shb is an integral component of the T‐cell receptor (TCR) signalling complex and in the absence of Shb the TCR is less responsive to stimulation, resulting in the preferential development of Th2 responses under conditions of in vitro stimulation. In the present study, we extend those observations to an in vivo situation using a murine model of atopic dermatitis. Shb knockout mice develop more pronounced symptoms of atopic dermatitis with increased localized oedema, epidermal hyperplasia and IgE production. Dermal infiltration of mast cells, eosinophils, CD4+ Th cells and F4/80+ macrophages was also significantly increased in Shb‐deficient mice. This correlated with elevated transcription of the hallmark Th2 cytokines interleukin‐4 and interleukin‐5. The loss of Shb therefore alters TCR signalling ability, thereby favouring the development of Th2‐driven inflammation and exacerbating symptoms of allergy.